Analisis Kelayakan Lokasi Tempat Pemrosesan Akhir (TPA) Baru Rumbai Pengganti TPA Muara Fajar Kota Pekanbaru - Choirus Subechan; Zulfan Saam; Tengku Nurhidayah (Universitas Riau, 2017)
This research was conducted from April to October 2015 and located in a new landfill in the District of Rumbai Pekanbaru. The purpose of this study is to analyze the parameters of the landfill site selection based on SNI 03-3241-1994 and feasibility (in the environmental, social, and economic) in District of Rumbai as substitute final waste processing site Muara Fajar. This type of research is descriptive and comparative survey method. Data needs, including primary data obtained through filling the questionnaire by respondents and secondary data. The amount of sample is 19 respondents who were around the new landfill. Data processing is divided into processing of quantitative and qualitative data were processed using descriptive method. The data analysis technique used in this research is the analysis of quantitative and qualitative with the analysis method of scoring. Tassel feasibility of a new landfill site as substitute final waste processing site Muara Fajar, based on the criteria of SNI and the results of a critical analysis of SK SNI is feasible